2010 39th International Conference on Parallel Processing 2010
DOI: 10.1109/icpp.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

SAM: A Semantic-Aware Multi-tiered Source De-duplication Framework for Cloud Backup

Abstract: Existing de-duplication solutions in cloud backup environment either obtain high compression ratios at the cost of heavy de-duplication overheads in terms of increased latency and reduced throughput, or maintain small de-duplication overheads at the cost of low compression ratios causing high data transmission costs, which results in a large backup window. In this paper, we present SAM, a Semantic-Aware Multitiered source de-duplication framework that first combines the global file-level de-duplication and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…According to the results shown in Table II, we obtain two key observations. [21] and Microsoft's study [2], have similar observations. Meanwhile, there are remaining substantial duplicate chunks inside users.…”
Section: Observation and Motivationsupporting
confidence: 54%
See 1 more Smart Citation
“…According to the results shown in Table II, we obtain two key observations. [21] and Microsoft's study [2], have similar observations. Meanwhile, there are remaining substantial duplicate chunks inside users.…”
Section: Observation and Motivationsupporting
confidence: 54%
“…One-set was collected from 11 graduate students of a research group and was reported by Xia et al [32]. Inc-set was collected from initial full backups and subsequent incremental backups of 6 members of a university research group and was reported by Tan et al [21]. Full-set consists of 380 full backups of 19 researchers' PC and is reported by Xing et al [33].…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Particularly, there is communication between client software and the backup server to check for the presence of files or blocks (Harnik et al, 2010). Two well-known source de-duplication methods, source local chunk-level deduplication (Tan et al, 2010) and source global chunklevel de-duplication have been proposed in the past to address the above mentioned problem by erasing the redundant data chunks before transfering them to the remote backup destination.…”
Section: Introductionmentioning
confidence: 99%
“…Chun-Ho Ng's LiveDFS focused on the deduplication of VM image in the Open-Source cloud and achieved at least 2 International Journal of Distributed Sensor Networks 40% of storage saving for VM images storage with reasonable performance [11]. SAM [12] is a semantic-aware multitiered source deduplication framework for cloud backup system. It gets a high deduplication ratio which is as better as global chunk-based deduplication and very low overhead than that of global chunk-based deduplication.…”
Section: Introductionmentioning
confidence: 99%